JOURNALISTS' ETHICAL DILEMMA IN APPLYING DEONTOLOGICAL PRINCIPLES TO THE NEWS PRODUCTION PROCESS IN THE ERA OF TECHNOLOGICAL DETERMINISM (Case Study of INDOZONE.id and GATRA.com Journalists - Fahmy Fotaleno; Udi Rusadi; Asrul Mustaqim (Bajang Institute, 2024)
In an ever-changing and evolving media environment, this dilemma becomes increasingly complex and challenging. On one hand, the adherence to journalistic ethical codes is crucial to ensure the accuracy, balance, and integrity of the information conveyed to the public. However, on the other hand, the pressure to compete in delivering news as quickly as possible, particularly in the digital era where information can spread rapidly, often hampers efforts to adhere to these ethical codes. Therefore, the updating of journalistic ethical codes in the age of technological advancement becomes crucial. Responsiveness to dynamic changes in the media environment is key to maintaining the relevance and sustainability of ethical principles in journalistic practice.